Calcareous nannofossil biostratigraphy of the Late Cretaceous‒early Paleocene interval in the Zagros basin (southeastern Tethys), Iran. Issue 1 (2nd January 2021) - Mahanipour, Azam; Parandavar, Mohammad; Youssef, Mohamed
Abstract: Calcareous nannofossil biostratigraphy reveals a continuous depositional record through the Upper Cretaceous‒Paleocene succession in the Zagros Basin; southwest Iran (southeastern part of the Neo-Tethys), especially through the Cretaceous‒Paleogene and the Danian‒Selandian boundaries. The upper part of the Gurpi Formation and the lower part of the Pabdeh Formation were investigated. Calcareous nannofossil assemblages from these formations are characterized by abundant, diverse and moderate- to well-preserved forms with Tethyan affinities. This study concentrates on two sections (the Gurpi and Kabir-Kuh sections) in the west and southwest of Iran in the Zagros Basin, which span biozones CC25c/UC20bTP to NP6/NTp10B in the Kabir-Kuh and CC25b/UC20aTP to NP5/NTp9 in the Gurpi section. Late Maastrichtian nannofossil abundance and diversity in the studied intervals is high with a sharp decrease slightly above the K/Pg boundary. The K/Pg boundary interval is marked by the FO of Biantholithus sparsus, an acme of the dinoflagellate cyst Thoracosphaera operculata, a notable decrease in Cretaceous calcareous nannofossil abundance and diversity, and the appearance of new Paleocene taxa. An increased abundance of Thoracosphaera is recorded similar to that in the El Kef (Global Stratotype Section and Point, GSSP, for the K/Pg boundary), Ellés (auxiliary section), Egypt, Atlantic Ocean and sections elsewhere in the world. Reworked Cretaceous calcareous nannofossils are recorded from the base of the Danian along with the new Paleocene species. The Danian‒Selandian boundary is marked by the appearance of Lithoptychius ulii, Lithoptychius pileatus and Lithoptychius janii at the base of NTp8C; this level is also marked by the second radiation of Fasciculithus . Azam Mahanipour [a_mahanipour@uk.ac.ir ], Department of Geology, Faculty of Science, Shahid Bahonar University of Kerman, Kerman, Iran; Mohammad Parandavar [parandavar.m@gmail.com ], Paleontological Research Department, Exploration Directorate of Oil and Gas, NIOC, Tehran; Mohamed Youssef [myousefgeology@gmail.com ], Department of Geology, Faculty of Science, South Valley University, 83523 Qena, Egypt.